Jitter-correction for IR/UV-XUV pump-probe experiments at the FLASH free-electron laser - Savelyev, E; Boll, R; Bomme, C; Schirmel, N; Redlin, H; Erk, B; Düsterer, S; Müller, E; Höppner, H; Toleikis, S; Müller, J; Kristin Czwalinna, M; et al. (IOP Publishing, 2017)
In pump-probe experiments employing a free-electron laser (FEL) in combination with a synchronized optical femtosecond laser, the arrival-time jitter between the FEL pulse and the optical laser pulse often severely limits the temporal resolution that can be achieved. Here, we present a pump-probe experiment on the UV-induced dissociation of 2,6-difluoroiodobenzene (C6H3F2I) molecules performed at the FLASH FEL that takes advantage of recent upgrades of the FLASH timing and synchronization system to obtain high-quality data that are not limited by the FEL arrival-time jitter. We discuss in detail the necessary data analysis steps and describe the origin of the time-dependent effects in the yields and kinetic energies of the fragment ions that we observe in the experiment.